Adding cognition to AT(N) models improves prediction of cognitive and functional decline. Issue 1 (31st March 2021) - O'Shea, Deirdre M.; Thomas, Kelsey R.; Asken, Breton; Lee, Athene K.W.; Davis, Jennifer D.; Malloy, Paul F.; Salloway, Stephen P.; Correia, Stephen; ,
Abstract: Introduction: This study sought to determine whether adding cognition to a model with Alzheimer's disease biomarkers based on the amyloid, tau, and neurodegeneration/neuronal injury—AT(N)—biomarker framework predicts rates of cognitive and functional decline in older adults without dementia. Methods: The study included 465 participants who completed amyloid positron emission tomography, cerebrospinal fluid phosphorylated tau, structural magnetic resonance imaging, and serial neuropsychological testing. Using the AT(N) framework and a newly validated cognitive metric as the independent variables, we used linear mixed effects models to examine a 4‐year rate of change in cognitive and functional measures. Results: The inclusion of baseline cognitive status improved model fit in predicting rate of decline in outcomes above and beyond biomarker variables. Specifically, those with worse cognitive functioning at baseline had faster rates of memory and functional decline over a 4‐year period, even when accounting for AT(N). Discussion: Including a newly validated measure of baseline cognition may improve clinical prognosis in non‐demented older adults beyond the use of AT(N) biomarkers alone.